Development of Digital Resources in Increasing the Efficiency of Teaching the Mother Language in Academic Lyceums (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article aims to organize lesson processes in an interactive way that is one of the requirements of the modern educational system, as well as to create a guide to fully convey knowledge to the student with an understanding of the content of Education. Academic lyceums, which are the middle link of their education, provide information about several techniques that can be used to teach their native language. Today, the main goal of education is to provide the student with certain theoretical knowledge for a short period of time, to develop skills and competencies in them in relation to certain activities, as well as to control the activities of students, to assess the level of related knowledge, skills and qualifications, high pedagogical skills and in relation to the educational process it aims to achieve greater results in the bundan by introducing approaches to the educational system.